Dampak Perubahan NJOP PBB-P2 Berdasarkan Keputusan Walikota Pematangsiantar Nomor: 900.1.13.1/1210/Ix/2024 terhadap Pelaksanaan Tugas PPAT dalam Peralihan Hak atas Tanah dan Bangunan di Kota Pematangsiantar - Frans Edison Sihombing; Henry Sinaga; tony (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The amendment to the Taxable Sale Value (NJOP) of Land and Building Tax (PBB-P2) based on the Decree of the Mayor of Pematangsiantar Number 900.1.13.1/1210/IX/2024 has significantly impacted the performance of Land Deed Officials (PPAT) in the transfer of rights over the land and the buildings. The increase in NJOP, reaching up to 1,000%, has sparked public controversy by raising the burden of Land and Building Rights Acquisition Duty (BPHTB) and impeding the smooth flow of transactions. Employing a normative-empirical method with qualitative analysis, this study finds that the policy is legally valid yet problematic in its implementation, particularly concerning legal certainty, transparency and justice. Policy evaluation and a clear objection mechanism are needed to balance regional revenue optimization with the protection of taxpayers' rights.